Effect of alloying oxygen on the microstructure and mechanical properties of Zr-based bulk metallic glass. (November 2021) - Zhou, W.H.; Duan, F.H.; Meng, Y.H.; Zheng, C.C.; Chen, H.M.; Huang, A.G.; Wang, Y.X.; Li, Y.
Abstract: Due to the high solubility limit of oxygen in Zr, dissolution of oxygen in the Zr-based alloys is unavoidable. However, as an alloying element, the effect of oxygen on the microstructure and mechanical properties of monolithic Zr-based bulk metallic glasses (BMGs) is rarely reported. Here, we systematically investigated the evolution of microstructure and mechanical properties of monolithic Zr61 Cu25 Al12 Ti2 BMGs with alloying oxygen content ranging from 650 at. ppm to 5600 at. ppm. With increasing oxygen content from 650 at. ppm to 3500 at. ppm, the compressive plasticity only decreased slightly, from 2.00±0.85% to 1.60±0.91%; however, it plunged to 0.77±0.33% when the oxygen content was further increased to 5600 at. ppm. The threshold oxygen content level for the ductile-brittle transition was revealed at 3500 at. ppm, and the embrittlement at high oxygen content is closely related with a number of changes in microstructure: sharply increases in the size of shear transformation zone (STZ) and in the degree of local ordering, including the imperfect ordered packing (IOP) atomic clusters and large medium-range ordering (MRO) domains. The above findings not only advance the understanding of the effect of alloying oxygen on the microstructure and mechanical properties, but also help to design Zr-based BMGs with excellent performance, promoting their wider commercial application. Graphical Abstract: Image, graphical abstract